Reframing masculinities : narrating the supportive practices of men - Chopra, Radhika; UNIFEM South Asia Regional Office, New Delhi; Zonta International (Hyderabad : Orient Longman, 2007)
With reference to India; contributed articles.
Includes bibliographical references.
Keywords: Men -- India -- Attitudes; Masculinity -- India